Executive Aggrandisement and Democratic Regression in Indonesiaâ€™s Jokowi Administration - Agustino, Leo; Sylviana, Mona; Andalus, Mutia Kartika (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
At the end of 2019, COVID-19 Pandemic has been devastated almost whole of human life sector, including politics and nations. COVID-19 Pandemic existence has urged the onset of misuse of power in several countries that have aÂ  weak democracy with â€œemergency policyâ€ or â€œdiscretional rulesâ€, as if it become an opportunity for the government to do the agenda-setting towards illiberal polict without having mobilization concern or opositions counter (Schenkkan 2020). This articleÂ  aim to explore how executiveâ€™s power aggrandisement that was happened in the 2th period of Jokowiâ€™s administrative as a contribution of democracry degradation in Indonesia. With theÂ  use of library research, that examine various literature, such as book, journal, report that relevan to the research topics (Neuman 2014), Author explore the data regarding the executive aggrandisement in the 2th period of Jokowiâ€™s Administrative. The result of this research is democracy degradation or democrary backslidingÂ  happened during Jokowiâ€™s Administatrative was instigated with several factors which is division of power, executive aggrandisement, and the discourse of 3th period of Jokowiâ€™s administration.